2013
DOI: 10.1016/j.psyneuen.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Yogic meditation reverses NF-κB and IRF-related transcriptome dynamics in leukocytes of family dementia caregivers in a randomized controlled trial

Abstract: Background Although yoga and meditation have been used for stress reduction with reported improvement in inflammation, little is known about the biological mechanisms mediating such effects. The present study examined if a yogic meditation might alter the activity of inflammatory and antiviral transcription control pathways that shape immune cell gene expression. Methods Forty-five family dementia caregivers were randomized to either Kirtan Kriya Meditation (KKM) or Relaxing Music (RM) listening for 12 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
200
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(212 citation statements)
references
References 51 publications
9
200
2
1
Order By: Relevance
“…These findings demonstrate a causal effect of prosocial behavior on leukocyte gene regulation, and they contribute to a growing body of literature mapping the molecular pathways that may link prosocial behavior to physical health. These findings also add purposeful engagement in prosocial behavior to the small list of other interventions that have previously been found to reduce CTRA gene expression (e.g., meditation, yoga, and cognitivebehavioral stress management; Antoni et al, 2012;Black et al, 2013;Bower et al, 2014;Creswell et al, 2012;Irwin et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…These findings demonstrate a causal effect of prosocial behavior on leukocyte gene regulation, and they contribute to a growing body of literature mapping the molecular pathways that may link prosocial behavior to physical health. These findings also add purposeful engagement in prosocial behavior to the small list of other interventions that have previously been found to reduce CTRA gene expression (e.g., meditation, yoga, and cognitivebehavioral stress management; Antoni et al, 2012;Black et al, 2013;Bower et al, 2014;Creswell et al, 2012;Irwin et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…This concept has recently been applied to a single participant who was characterized in-depth over the period of 532 days for dynamics of brain function and their relation to psychological and biological parameters (Poldrack et al 2015). Molecular profiles related to well-being can also serve as endpoints in intervention studies for promoting happiness, as recently shown for a Yoga intervention that was able to reduce inflammation-related biomarkers among fatigued breast cancer survivor (Irwin et al 2014) and family dementia care givers (Black et al 2013). Finally, genetic determinants of happiness-related phenotypes can provide new insights into the molecular basis of happiness.…”
Section: A First Research Question Is About Molecular Profiling Of DImentioning
confidence: 99%
“…Transcriptional profiles show that peripheral blood leucocytes reduce the pro-inflammatory nuclear factor (NF) and increase anti-viral interferon responses. The expression of 68 genes is changed, most with down and some with up regulation (Black et al 2012). In peripheral blood monocyte cells, mindfulness meditation reduces the expression of histone deacetylase genes and the expression of inflammatory genes suggesting a potential for the treatment of chronic inflammatory conditions (Kaliman et al 2014).…”
Section: Benefits Of Meditationmentioning
confidence: 99%